The Impact Of Assets Revaluation On Corporate Performance In Australian Industrial Companies An Empirical Study - BASUKI, BASUKI (The International Journal of Accounting and Business Society, 1994)
Revaluation of Non-Current Assets is a topic of interest, because it is no longer discussed and practised in many countries. Upward revaluation, indeed, has been effectively banned in the United States, in contrary, Australia, Canada, New Zealand and the United Kingdom still allow such practices. This research is undertaken to answer the question whether revaluation of non-current assets is associated with superior or inferior company performance. The results indicate that revaluation of non current assets does not show any relationships with the company’s performance and does not indicate either superior or inferior company performance. Keywords: Financial Accounting, Assets Revaluation, Australian Accounting Standard.